Selective pressure on microbial communities in a drinking water aquifer – Geochemical parameters vs. micropollutants. (15th April 2022) - Aldas-Vargas, Andrea; Hauptfeld, Ernestina; Hermes, Gerben D.A.; Atashgahi, Siavash; Smidt, Hauke; Rijnaarts, Huub H.M.; Sutton, Nora B.
Abstract: Groundwater quality is crucial for drinking water production, but groundwater resources are increasingly threatened by contamination with pesticides. As pesticides often occur at micropollutant concentrations, they are unattractive carbon sources for microorganisms and typically remain recalcitrant. Exploring microbial communities in aquifers used for drinking water production is an essential first step towards understanding the fate of micropollutants in groundwater. In this study, we investigated the interaction between groundwater geochemistry, pesticide presence, and microbial communities in an aquifer used for drinking water production. Two groundwater monitoring wells in The Netherlands were sampled in 2014, 2015, and 2016. In both wells, water was sampled from five discrete depths ranging from 13 to 54 m and was analyzed for geochemical parameters, pesticide concentrations and microbial community composition using 16S rRNA gene sequencing and qPCR. Groundwater geochemistry was stable throughout the study period and pesticides were heterogeneously distributed at low concentrations (μg L −1 range). Microbial community composition was also stable throughout the sampling period. Integration of a unique dataset of chemical and microbial data showed that geochemical parameters and to a lesser extent pesticides exerted selective pressure on microbial communities. Microbial communities in both wells showed similar composition in the deeper aquifer, where pumping results in horizontal flow. This study provides insight into groundwater parameters that shape microbial community composition. This information can contribute to the future implementation of remediation technologies to guarantee safe drinking water production. Graphical abstract: Image 1 Highlights: Groundwater geochemistry is stable in time, micropollutant concentrations fluctuate. Groundwater geochemistry shapes microbial communities more than micropollutants. The most influential geochemical parameters are DOC, NO3 −, Fe (II) and SO4 2- . Deep aquifer microbial communities are similar, indicating hydrological connection.